Ali Reynolds : Unfinished business - Book 20 Book 16 - Jance, J. A. (Judith A.) (New York, New York : Gallery Books, an imprint of Simon & Schuster, Inc., 2021)
"Ali Reynoldss personal life is in turmoil when two separate men show up on the scene: a serial killer and a former employee of her husbands who has just been released from a sixteen-year prison sentence for murdering his girlfriend. With lives hanging in the balance, Ali must thread the needle between good and evil"--
Keywords: Reynolds, Ali (Fictitious character) -- Fiction; Beaumont, J. P. (Fictitious character) -- Fiction; Private investigators -- Fiction; Murder -- Investigation; Fiction; Judicial error -- Fiction; Parolees -- Fiction; Serial murderers -- Fiction; Missing persons -- Fiction; Mystery